Arm current reversal‐based modular multilevel DC‐DC converter. Issue 6 (22nd March 2021) - Nazih, Yousef; Hossam‐Eldin, Ahmed; Elserougi, Ahmed
Abstract: Nowadays, most of the converters used in high‐power high‐voltage (HV) applications are the conventional modular multilevel converters (MMC). However, in the case of DC‐DC conversion, an imbalance of the capacitor voltages occurs and the conventional MMC fails to operate correctly. This paper introduces an arm current reversal‐based modular multilevel DC‐DC converter, which successfully provides balance among the capacitor voltages while operating in DC‐DC conversion. The proposed configuration is used in medium voltage DC grids to feed DC loads or to interconnect between two DC grids of different voltage levels. The proposed converter is a two‐stage DC‐DC modular converter, which consists of a single‐phase half‐bridge MMC with half‐bridge submodules (HBMMC) followed by a single‐phase H‐bridge MMC with half‐bridge submodules (SMs). The operational concept of the proposed converter is based on reversing the arm current direction and reversing the output terminals with the help of the H‐bridge MMC stage, which ensures the same direction of the voltage at the load terminals. The proposed converter provides a high conversion ratio, bidirectional power flow, simple architecture, and a simple control scheme. Detailed illustrations, analysis, and design of the proposed converter are presented. Besides, MATLAB‐based and Opal RT‐based simulation results and experimental results are presented to validate the proposed configuration claims.